Estimation of uncertainty measurement of parameters of thr external magnetic field of technical means - Дегтярьов, О. В.; Запорожець, О. В. (Харківський національний університет повітряних сил імені Івана Кожедуба, 2018)
A methodology for estimating the uncertainty of indirect measurements of the magnitude of the magnetic mo-ment created by an external magnetic field of a technical device is proposed. Previously, to estimate the measured value, direct, multiple measurements of the useful signal were performed. The measurements were performed at eight points with different coordinates. An induction type sensor was used for the measurements. Direct measure-ments were also made of the distance from the geometric center of the magnetic field source under investigation to the sensor. Model equation is completed. The specification of measurements is made. An uncertainty budget for measuring the magnetic moment has been compiled. Found the total uncertainty of measuring the magnetic moment. Extended uncertainty found.
Keywords: measurement uncertainty; indirect measurement; magnetic momen; induction sensor; uncertainty budget